Niveles de concentración de hemoglobina en lactantes de 6 meses de edad con clampaje tardío y precoz de cordón umbilical. Hospital Distrital Santa Isabel de El Porvenir, periodos julio a diciembre 2019 y julio a diciembre 2020 - Mendoza Rodriguez, Milene Roxana (2022)
The low concentration of Hemoglobin in children as a consequence of iron deficiency, leads to increased causes of infant death, and dysfunction of cognitive, motor and behavioral development. Likewise, it will condition disorders in the maturation process, as well as auditory and visual dysfunction. It is known that the basic structure of the brain is consolidated in the first years of life, due to the fact that at this stage its development occurs with greater speed. Paradoxically, at this stage there is also greater fragility due to external factors produced from gestation and initial extrauterine life. In Peru, low hemoglobin concentration in infants is a public health problem; of serious category, due to its prevalence in a percentage of 43.6% in children from 6 to 35 months of life. Faced with this problem, it is necessary to know and implement strategies in order to prevent iron deficiency anemia, one of them being clamping under the late technique of the umbilical cord. Proceeding to late clamping of the cord will allow the minor to provide himself with an iron reserve that will protect him during the 4 to 6 months of life. Health strategies are proposed by MINSA to prioritize care at the health level and establish different care mechanisms for people at the sectoral and institutional level, including late clamping of the umbilical cord as a specific consideration.